How human capital may boost competitive advantage in cafés? Findings from Bukittinggi - Gustiawan, Willson; Septivani, Mega Dwi; Afifah, Afifah; Sari, Maya Permata (ABEC Indonesia, 2024)
This study investigated the relationship between Human Capital (HC) and Competitive Advantage (CA) in thecoffee shop industry of Bukittinggi, a prominent tourist destination in West Sumatra. Utilizing a quantitative approach,primary data were collected through structured questionnaires distributed to 55 coffee shop owners. The researchemployed Structural Equation Modeling (SEM) with SmartPLS to analyze the data, aiming to elucidate how investmentsin human capital contributed to achieving competitive advantage in a highly competitive market. The findings indicated asignificant positive relationship between human capital and competitive advantage, highlighting the critical role ofemployee education, skills, and experience in enhancing business performance. Additionally, the study introduced socialcapital as a vital variable linked to networking within the coffee business community, which further supportedcompetitive advantage. The results emphasized the importance of developing human capital strategies for coffee shopowners to thrive in an evolving marketplace. These insights provided practical implications for l ocal entrepreneurs,policymakers, and stakeholders, suggesting that continued investment in human resources could foster business growthand positively impact the tourism sector in Bukittinggi. Ultimately, this research contributed to the broader understandingof human capital's role in driving competitive advantage within small and medium-sized enterprises (SMEs).